Perceptions on thermal comfort in general wards for Malaysian hospitals - Kushairi, A.A.A.; Mahyuddin, N.; Adnan, E.; Sulaiman, R. (Penerbit UKM, 2015)
Environmental Quality Perception (EQP) is constructed to help in environmental studies and as an assessment tool for the environment and behaviour field studies. Using EQP assessment method in the hospital environment studies helps to understand the relationship between people and the hospital environment. Achieving sufficient thermal comfort level in existing government hospital buildings were seriously considered especially in general wards where patients and staffs most spend time in. The assessments were completed by 120 respondents (i.e. patients and staff nurse) from five different general wards located in different blocks in a Malaysian public hospital. To assess perception validity, one is focusing on objective physical observation evaluating the hospital environment correlated with subjective evaluation through questionnaire on social environment. The main objective of this research is to investigate the users’ perceptions of existing thermal comfort quality in the different department’s general wards of existing government hospitals in providing comparative table showing the different performance of thermal comfort. Overall reliability on thermal satisfaction by the occupants shows significant differences in all identified variables that were influenced by location and characteristic of the buildings as well as the respondents demographic. Mixed method analyses were used whereby data responds were analysed by multivariate (MANOVA) and univariate (ANOVA) analyses of variance for quantitative and triangulation analyses were tabled down for qualitative between average responses of thermal comfort perceived with the hospital physical. The findings concluded with majority perceived moderation on most thermal comfort elements indicates that there were growing acceptance and tolerance with the space that are subjected to duration of admitted and hours of working. Therefore, further investigation should be carried out to enhance the probability in perceptions with multiple hospitals for clear comparisons.